2010
DOI: 10.1007/s10930-010-9235-7
|View full text |Cite
|
Sign up to set email alerts
|

Ternary System of Solution Additives with Arginine and Salt for Refolding of Beta-Galactosidase

Abstract: (L)-Arginine hydrochloride (Arg HCl) has been used for protein refolding as a universal aggregation suppressor for monomeric proteins. This paper presents an investigation of the refolding of tetrameric beta-galactosidase (beta-gal) using Arg HCl and other salts. In a binary system using only Arg HCl, the refolding yield of beta-gal increased with increasing concentration up to 0.2 M. However, the refolding yield sharply decreased above this concentration, reaching the level below the control yield of 5% at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…We have also shown that Arg enhances refolding of monomeric [10] and oligomeric proteins [19], and inhibits heat-induced aggregation [9],[10],[12],[13]. It has been suggested that such effects of Arg are due to the ability to solubilize aggregation-prone denatured proteins [20], as also indicated by the enhancement of solubility of hydrophobic small compounds by Arg [21][24].…”
Section: Introductionmentioning
confidence: 64%
“…We have also shown that Arg enhances refolding of monomeric [10] and oligomeric proteins [19], and inhibits heat-induced aggregation [9],[10],[12],[13]. It has been suggested that such effects of Arg are due to the ability to solubilize aggregation-prone denatured proteins [20], as also indicated by the enhancement of solubility of hydrophobic small compounds by Arg [21][24].…”
Section: Introductionmentioning
confidence: 64%
“…We have developed the application of ArgHCl for suppressing aggregation and adsorption of various proteins during heat treatment and oxidative refolding (16)(17)(18)(19)(20)(21)(22). These effects have been ascribed, at least in part, to the interaction of aromatic groups on arginine with the protein surface (23).…”
mentioning
confidence: 99%
“…After the discovery, Arg has been use for the refolding of many medical proteins, including immunotoxin from monoclonal antibody fused with Pseudomonas exotoxin A [37], truncated tissue-type plasminogen activator [38], rabbit heterotetrameric casein kinase II [39], interleukin-6 receptor [40], Psedomonas fluorescens lipase [41], human neurotrophin-3 [42], human and mouse single-chain Fv fragments [43], human interleukin-21 [44], and human interleukin-10 [45]. Furthermore, Arg-assisted refolding technology has been practically enhanced for "step-wise dilution" [46], the synergistic effect of Arg with kosmotropic ions [47] or a weak detergent of lauroyl-L-glutamate and Arg [48] and on the column refolding of a monomeric noncollagenous domain of Type IV collagen [49].…”
Section: Arginine Is a Versatile Additive That Prevents Physical Aggrmentioning
confidence: 99%
“…Similarly, Arg promotes heat-induced aggregation for the large immunoglobulin G1 protein [82] and the β-lactoglobulin (βLG) oligomeric protein [74]. Such structurally unstable proteins can be stabilized by the use of Arg with the acidic amino acids Glu and Asp [82] and the kosmotropic ions [47]. Thus, it is possible that Arg promotes the heat-induced aggregation of large and complex proteins at low concentration.…”
Section: Arginine Is a Versatile Additive That Prevents Physical Aggrmentioning
confidence: 99%